Uptake of 2-Oxoglutarate in Synechococcus Strains Transformed with the Escherichia coli kgtP Gene - Vázquez-Bermúdez, María Félix (American Society for Microbiology, 2000)
A number of cyanobacteria from different taxonomic groups exhibited very low levels of uptake of 2-[U-(14)C]oxoglutarate. Synechococcus sp. strain PCC 7942 was transformed with DNA constructs carrying the Escherichia coli kgtP gene encoding a 2-oxoglutarate permease and a kanamycin resistance gene cassette. The Synechococcus sp. strains bearing the kgtP gene incorporated 2-oxoglutarate into the cells through an active transport process. About 75% of the radioactivity from the 2-[U-(14)C]oxoglutarate taken up that was recovered in soluble metabolites was found as glutamate and glutamine. 2-Oxoglutarate was, however, detrimental to the growth of a Synechococcus sp. strain bearing the kgtP gene.